A review on vibration characteristics of additively manufactured metal alloys - Azher, Kashif; Shah, Mussadiq; Bakhtari, Ahmad Reshad; Castelluccio, Gustavo M.; Tüfekci, Celal Sami; Cini, Andrea; Akturk, Nizami; Salamci, Metin U. (Wiley, 2024)
The advent of additive manufacturing (AM) has dramatically shifted the manufacturing sector conceptualization, design, and creation of products. AM can facilitate the production of complicated geometries and create functioning components with distinctive features for aerospace and automotive applications. However, defects such as pores, voids, interfaces, and inclusions can impair the quality and functionality of AM components. Vibration analysis (VA) has become a popular tool for the dynamic qualification and testing of products and nondestructive testing, but the literature lacks a comprehensive review of VA applied to AM. Hence, in this article, recent advances in the application of VA for identifying and characterizing flaws in metal alloys, including titanium, aluminum, and nickel-based alloys produced by AM, are summarized. In this review, studies on defects such as porosity, cracks, and inclusions and their effect on VA are also included. Herein, this article concludes with a discussion of the limitations of VA for defect characterization and future research directions. Overall, VA is a promising nondestructive testing method for quality assurance in AM and offers insights on overcoming the difficulties for further development and application of this technology.
Keywords: additive manufacturing; frequencies; geometries; modal analyses; orientations; process parameters; vibrations